Into the Gateway: the Rhetoric Society of America Project on Power, Place, and Publics. Issue 2 (2nd April 2020) - Chaput, Catherine; Olman, Lynda; Pason, Amy
ABSTRACT: This is the Guest Editors' Introduction to a themed issue that reflects on the inaugural Rhetoric Society of America Project, which, in 2019, hosted a range of rhetorical investigations into the University of Nevada, Reno's Campus Master Plan and its Gateway Precinct. It argues that the recent field orientation to rhetoric pushes rhetoricians to think about how their scholarship might participate in immanent negotiations, mixing slow, deliberate, and thoughtful rhetorical analyses with fast, spontaneous, and instinctual demands. Using the Project as an example, it suggests that the participatory act of being in the field cannot be removed from the rubric of power, place, and publics.